RESPON ULAMA SUMATERA BARAT TENTANG TALAK DI LUAR PENGADILAN AGAMA - Purnama Rusana (Fakultas Syariah dan hukum Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The problem in this research is differences in the provisions in fiqh and positive law regarding the position of divorce outside the Religious Courts. This also happened to the difference in fatwas issued by Islamic organizations, namely Muhammadiyah and Nahdatul Ulama. The purpose of this study was to determine the response of West Sumatran ulama regarding the position of talak outside the Religious Courts and to know the arguments used by West Sumatran scholars regarding talak outside the Religious Courts. This research is field research. Data collection techniques through interviews and documentation.The results of the research can be summarized as follows: first, the response of ulama in West Sumatra regarding the position of talak outside the Religious Courts is that most of them state that it is illegal to do divorce outside the Religious Courts. 14 (fourteen) informants whom the author interviewed 11 (eleven) of whom agreed that a divorce was only legal when before the Religious Court. 3 (three) other informants were of the opinion that talak outside the Religious Court is legal. Second, the arguments used by West Sumatran ulama in various opinions, namely: informants who have a valid opinion outside the Religious Court argue with the hadith and from a fiqh point of view. Meanwhile, the informant who views divorce as illegitimate outside the Religious Court argued with the al-Quran and al-Sunnah, the method of ijtihad and the principles of fiqh.Kata Kunci : Ulama, Talak, Pengadilan Agama